The plausibility of Proverbs 31 as final parental (motherly) instruction - Sampson, Ndoga S. (Journal for semitics, 2014)
Proverbs 31 has been viewed as two separate poems: 31:1-9, the words of Lemuel's mother, and 31:10-31, an acrostic poem on the capable wife. Careful analysis of the two poems shows that these were juxtaposed by the redactor as a single composition through lexical and thematic links. It is equally observable that there is no title between the two compositions. Other than the shift in style where the first nine verses are prescriptive and the final 22 verses are descriptive, there is no indication to treat the two as separate. From these indicators, this paper seeks to argue for the plausibility of the final chapter as the final parental (motherly) instruction in which these formerly independent compositions are juxtaposed by the redactor for that specific purpose. This view will obviously yield some interpretational implications on the book of Proverbs that we would like to table for ongoing analysis.